Relationship between invasive hemodynamics and liver function in advanced heart failure. (3rd September 2019) - Vishram-Nielsen, Julie K. K.; Deis, Tania; Balling, Louise; Sabbah, Muhammad; Boesgaard, Søren; Rossing, Kasper; Wolsk, Emil; Gustafsson, Finn
Abstract: Objective . To examine how liver function (LF) relates to invasive hemodynamics cross-sectionally and longitudinally, in advanced heart failure (AHF) patients treated with maximally tolerated medical HF therapy. Design . A retrospective study of 309 consecutive AHF patients with a left ventricular ejection fraction < 45% treated with maximally tolerated medical HF therapy who were referred for AHF therapies. All patients underwent right heart catheterization (RHC) using Swan-Ganz catheters. Cardiac output was measured using thermodilution. Measurements of pulmonary capillary wedge pressure (PCWP), central venous pressure (CVP), cardiac index (CI) and mean arterial pressure (MAP) were obtained. RHC and evaluation of LF were repeated (median (IQR) = 186.5 (150–208) days) in 33 patients. Results . Mean (SD) age was 50 (±13) years, and 239 (77%) were men. Only 22 (7%) were treated with inotropes, and none were receiving mechanical circulatory support. Median (IQR) plasma alanine transaminase (ALT) was 32 (22–53) U/l, alkaline phosphatase (ALP) 82 (63–122) U/l, bilirubin 14 (9–22) µmol/l, albumin 39 (35–43) g/l, lactate dehydrogenase 212 (175–275) U/l, and the prothrombin time/International Normalized Ratio (PT/INR) 1.1 (1.0–1.3). In multivariate analyses significant associations between LF tests and hemodynamics were seen for CVP: ALP ( β = 0.031, p = .0002), bilirubin ( β = 0.027, p = .004), and INR ( β = 0.013, p = .002). PCWP ( β = 0.020, p = .002) and CI ( β = –0.17, p = .005) were also associated with bilirubin. Over time, changes in bilirubin correlated positively with changes in CVP ( β = 1.496, p = .005). Conclusion . In optimally treated AHF patients, CVP was associated with both markers of biliary excretion and liver synthesis function, whereas changes in CVP were associated with changes in markers of biliary excretion. Decongestion may improve measures of LF in AHF.